O critério constitucional da finalidade da contribuição de intervenção no domínio econômico - Moysés, Isabella Costa (2009)
The aim of the present dissertation consists in analyzing the finalistic criteria of the intervention contribution in the economic domain and shows the legal effects in case the purpose is not observed by the legislator in the process of positivation of norms. Therefore, positive law was delimited as object of study. Once the methodological cut was defined, language was set as the condition of knowledge. In the case of positive law, juridical reality is constituted by prescriptive language. Indispensable for the analysis of the criteria purpose of interventive contribution, the concepts of utterance, norm and its subspecies, giving highlight to the norm of normative production were developed. Once the Brazilian Tax Constitutional System was analyzed, tax classification and, consequently, the study of the pertinence relation between intervention contribution and taxation system was possible. After establishing the contribution of the intervention in the economic domain as tax sub specie, we started the interpretation of the article 149 of the Federal Constitution and the building of the tributary incidence matrix-rule. The criteria were described with the objective of enabling the study of the relation of coordination between incidence pattern norm and purpose norm. The applicable principles of taxation to the interventive contribution were highlighted as well as the principles related to the economic order. It was noticed that once the interventive contribution was made, the legislator should use the proceeds of collection to finance the intervention of the state in the economic domain, being it private activities. The State acts in the field of private activities and, even if it is with the objective of encourage, it must act only for the time lapse needed to establish the sector that is being intervened. It was found that it is not enough for the agent to set the criteria of the matrix-rule for the interventive contribution to be established validly. It is also necessary to respect the purpose criteria. The contribution of the intervention in the economic domain must be established, if necessary, to the development of a determined private sector and if it is characterized as the best way of doing it. It was shown that the simple purpose of collecting does not authorizes the creation of the tax. This is the reason why the proceeds of collection must be totally destined to the cost of the public regulation. The misapplication of the purpose in the process of positivation of norms invalidates the interventive contribution, and if properly set up in the system, but with an effective deviation of the amount collect, constitutes illicit that authorizes the punishment of the agent. Based on the study, some intervention contributions in the economic domain provided in the system were made